2020
DOI: 10.21037/tcr-20-3315
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of the prognostic role of cell adhesion molecules in acute myeloid leukemia

Abstract: Background:The outcomes for patients with acute myeloid leukemia (AML) have been shown to vastly differ, predominantly due to genetic heterogeneity. Cell adhesion molecules (CAMs) concluding numerous genes play an important role in AML. We aimed to systematically assess the expression characteristics of adhesion molecules and their correlation to the outcomes of AML.Method: A total of 173 patients with AML were enrolled in this study. The genetic expressional information and clinical data sourced in previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, ITGA4 expression was also detected on several healthy hematopoietic cells, which might impact the suitability of ITGA4 as a single target antigen. Studies on the prognostic role of ITGA4 expression in AML are very limited [31], thus we expect future studies to illuminate its role further.…”
Section: Discussionmentioning
confidence: 99%
“…However, ITGA4 expression was also detected on several healthy hematopoietic cells, which might impact the suitability of ITGA4 as a single target antigen. Studies on the prognostic role of ITGA4 expression in AML are very limited [31], thus we expect future studies to illuminate its role further.…”
Section: Discussionmentioning
confidence: 99%
“… 38 40 In a systematic analysis of cellular adhesion molecule expression signatures, additional data showed that ICAM2 was inversely associated with overall survival in AML patients, which further supported our results. 41 We demonstrated that patients with intermediate ELN-2017 risk were still significantly stratified by ICAM2 expression, which was an independent predictor of clinical outcome in multivariate regression analysis. There was a strong association between ICAM2 status and OS, even after accounting for age and the potential effects of bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 71%
“…Tryndyak et al reported that cytosine DNA hypermethylation induced the downregulation of CLDN14 gene expression in differentiated HepaRG cells treated with NaAsO 2 ( 64 ). Another study revealed that the CLDN14 expression level was negatively correlated with acute myeloid leukemia (AML) survival rates ( 65 ). In breast cancer (BC), CLDN14 gene expression was upregulated in BC tissues compared with non-cancer tissues, and a high gene expression of CLDN14 was associated with a poor overall survival ( 66 ).…”
Section: Discussionmentioning
confidence: 99%